Establishing a Sustainable Road Trauma Support Service in Western Australia - Breen, Lauren; O'Connor, Moira; Le, Anh (Australasian College of Road Safety, 2012)
Despite the clear psychosocial ramifications of road traffic crashes, there is no dedicated road trauma support service in Western Australia (WA). A road trauma support service in WA is urgently required to provide sustainable, coordinated, timely, and appropriate peer support and professional therapeutic interventions for road trauma victims, family members, witnesses, and for others who are adversely affected by road trauma. The objective of this paper is to describe an investigation of the mechanisms and costs associated with establishing a sustainable road trauma support service in WA. The study was guided by a stakeholder reference group comprising representatives from government and non-government agencies as well as community members affected by road trauma. Existing road trauma supports and services available in other Australian jurisdictions were examined to inform the establishment of a road trauma support service in WA. Three of these services were then visited by the first author to see firsthand the premises and resources and to talk to staff about each service. The investigation resulted in 22 recommendations outlining a ‘one-stop-shop’ that meets the varied needs of people in WA who are affected by road trauma.